Adherence in Diabetes Questionnaire (ADQ) score as predictor of 11-year HbA1c trajectories in children and adolescents with type 1 diabetes: A population-based longitudinal study. (March 2023) - Marks, Kevin P.; Birkebæk, Niels H.; Pouwer, Frans; Ibfelt, Else H.; Thastum, Mikael; Jensen, Morten B.
Abstract: Aims: To identify 11-year HbA1c trajectories in children/adolescents with type 1 diabetes and determine whether baseline caregiver- and/or child/adolescent-reported Adherence in Diabetes Questionnaire (ADQ) scores and multiple covariates predict HbA1c trajectory membership. Methods: For a 2009 population-based cohort of children/adolescents with type 1 diabetes, we analyzed HbA1c follow-up (2010−2020) data from Danish diabetes registries. HbA1c trajectories were identified with group-based trajectory modeling. Using multinomial logistic regression, we tested whether ADQ scores predicted trajectory membership when adjusting for sex, age at diabetes diagnosis, diabetes duration, family structure, and caregiver education. Results: For 671 children/adolescents (10–17 years at baseline) with 5644 HbA1c observations over 11 years, four trajectories/groups were identified: 1) "on target, gradual decrease" (27%), 2) "above target, mild increase then decrease" (39%), 3) "above target, moderate increase then decrease" (25%), and 4) "well above target, large increase then decrease" (9%). Using group one as the reference, lower caregiver-reported ADQ scores predicted group 2, 3, and 4 membership. Lower child/adolescent-reported ADQ scores predicted group 3 and 4 membership. Low caregiver education predicted group 3 and 4 membership. Single-parent status predicted group 4 membership. Conclusions: ADQ scores and socio-demographics may serve as tools to predict glycemic control in youth with type 1 diabetes. Highlights: Four distinct 11-year HbA1c trajectories were identified in youth with T1D. Lower youth adherence scores predicted the two highest risk HbA1c trajectories. Lower caregiver adherence scores predicted three higher risk HbA1c trajectories. Low caregiver education level predicted the two highest risk HbA1c trajectories. Single parent family status predicted the highest risk HbA1c trajectory.